Magneto – thermoelectric effects in quantum well in the presence of electromagnetic wave - Bau, Nguyen Quang; Hang, Dao Thu; Quang, Doan Minh; Nhan, Nguyen Thi Thanh (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2, 2017)
Abstract. We have studied magneto-thermoelectric effects in quantum well in the presence of electromagnetic wave. The analytic expression for Ettingshausen coefficient (EC) in the Quantum Well with parabolic potential (QWPP) in the presence of Electromagnetic wave (EMW) is calculated by using the quantum kinetic equation for electrons. The dependence of EC on the frequency, the amplitude of EMW, the Quantum Well parameters and the temperature are obtained. The results are numerically calculated, plotted, and discussed for GaAs/GaAsAl Quantum Well to clearly show the dependence of EC on above parameters and the results in this case are compared with the case in the bulk semiconductors. We realize that as the temperature increases, the EC decreases. The results show appearance of the Shubnikov–de Haas (SdH) oscillations when we survey the dependence of EC on the magnetic field.   Keywords:  Ettingshausen, Quantum well, Electromagnetic wave, parabolic potential, GaAs/GaAsAl.